Effect of ultraviolet light-emitting diode processing on fruit and vegetable-based liquid foods: A review - Salazar, Fernando; Pizarro-Oteíza, Sebastián; Kasahara, Ismael; Labbé, Mariela (Frontiers in Nutrition, 2022)
UV-LED technology has emerged as a non-thermal and non-chemical treatment for the preservation of liquid fruit and vegetable foods. This technology uses ultraviolet light to interact with the food at different wavelengths, solving problems related to product stability, quality, and safety during storage. UV-LED has been shown to affect microbe and enzyme inactivation, and it increases and helps retain bioactive compounds. Moreover, computational simulations are a powerful and relevant tool that can be used optimise and improve the UV-LED process. Currently, there are a limited amount of studies of this technology in liquid fruit and vegetable-based foods. This review gathers information on these food type and shows that it is a promising technology for the development of new products, environmentally friendly, and does not require the addition of chemicals nor heat. This is relevant from an industrial perspective because maintaining the nutritional and organoleptic properties ensures better quality. However, due to the scarce information available on this type of food, further studies are needed.